Whole-of-community interventions that address alcohol-related harms: protocol for a scoping review - Asha S George; Tanya Doherty; Mark Tomlinson; Nandi Siegfried; Ida Okeyo; Ulla Walmisley; Michelle De Jong; Carmen Späth; Nadine Harker (BMJ Open)
Introduction Alcohol-related harm is a rising global concern particularly in low-income and middle-income countries where alcohol use fuels the high rates of violence, road traffic accidents and is a risk factor for communicable diseases such as HIV/AIDS and tuberculosis. Existing evidence to address alcohol-related harm recommends the use of intersectoral approaches, however, previous efforts have largely focused on addressing individual behaviour with limited attention to whole-of-community approaches. Whole-of-community approaches are defined as intersectoral interventions that are systematically coordinated and implemented across the whole community. The objective of this scoping review is to synthesise the existing literature on multisectoral, whole-of-community interventions which have been used to modify or prevent alcohol-related harms.Methods and analysis This scoping review will follow the six-step approach that involves; (1) identifying the research question, (2) identifying relevant studies, (3) selecting studies, (4) charting the data, (5) collating, summarising and reporting the results and (6) expert consultation. Published literature from 2010 to 2021 will be accessed through PubMed, Web of Science, CINAHL Plus and Scopus databases. Search terms will focus on the concepts of ‘interventions’, ‘community-based’, ‘harm reduction’ and ‘alcohol’. There will be no restrictions on the type of study methodology or country of origin. Title and abstract followed by full-text screening will be conducted by two reviewers to identify relevant articles based on the inclusion and exclusion criteria. Data from selected articles will be extracted and charted in Excel software. Findings will be analysed qualitatively and presented using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis: Extension for Scoping Review.Ethics and dissemination This review makes use of published and publicly available data and no ethics approval is required. The results from this study will be disseminated via publication in peer-reviewed journals and presentations at relevant academic research fora and conferences.